2010
DOI: 10.1111/j.1752-7325.2009.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive dental utilization for Medicaid-enrolled children in Iowa identified with intellectual and/or developmental disability

Abstract: Objectives To compare preventive dental utilization for children with intellectual and/or developmental disability (IDD) and those without IDD and to identify factors associated with dental utilization. Methods We analyzed Iowa Medicaid dental claims submitted during calendar year (CY) 2005 for a cohort of children ages 3–17 who were eligible for Medicaid for at least 11 months in CY 2005 (n=107,605). A protocol for identifying IDD children was developed by a group of dentists and physicians with clinical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
55
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 25 publications
10
55
4
Order By: Relevance
“…The main dependent variable in our study was whether a child utilized any dental care in 2012, defined as the presence of any dental claim (84). In addition, we created four variables to represent different types of dental care using previously published criteria (84).…”
Section: Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main dependent variable in our study was whether a child utilized any dental care in 2012, defined as the presence of any dental claim (84). In addition, we created four variables to represent different types of dental care using previously published criteria (84).…”
Section: Study Variablesmentioning
confidence: 99%
“…In addition, we created four variables to represent different types of dental care using previously published criteria (84). Diagnostic care (e.g.…”
Section: Study Variablesmentioning
confidence: 99%
“…However, consistent with caries prevalence rates, only half as many low-income children receive sealants as their higher income peers (Dye et al, 2007). Previous studies have identified the enablers and barriers to preventive dental care services for publicly insured children (Chi and Milgrom, 2009;Chi et al, 2010;Rozier et al, 2010;Askelson et al, 2014). Only 1-in-3 state Medicaid programs reimburses dentists for primary molar sealants (Chi and Singh, 2013), which is a potential barrier to the receipt of sealants for low-income children.…”
mentioning
confidence: 99%
“…The main barriers are the child's behavior and the economic cost and the percentages and barriers are almost identical to those found in this study. However, in the United States it has been reported that, in spite of some barriers, access to preventive treatment for children with intellectual or development deficits is close to 50%, similar to that of children without these disorders 12 . On the other hand, the results of this study indicate that a third of such population attends only for check-up, very few only for emergency and they are mostly attended by pediatric dentists.…”
Section: Hernández C and Oyarzún Pmentioning
confidence: 99%
“…Second, there are no validated or at least widely used instruments to assess parents' perception about dental care. Therefore, an unprecedented survey, condensing the main issues reported in literature, was compiled [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Hernández C and Oyarzún Pmentioning
confidence: 99%